Improvement of charge-pumping electrically detected magnetic resonance and its application to silicon metal–oxide–semiconductor field-effect transistor. (15th December 2016) - Hori, Masahiro; Tsuchiya, Toshiaki; Ono, Yukinori
Abstract: Charge-pumping electrically detected magnetic resonance (CP EDMR), or EDMR in the CP mode, is improved and applied to a silicon metal–oxide–semiconductor field-effect transistor (MOSFET). Real-time monitoring of the CP process reveals that high-frequency transient currents are an obstacle to signal amplification for EDMR. Therefore, we introduce cutoff circuitry, leading to a detection limit for the number of spins as low as 10 3 for Si MOS interface defects. With this improved method, we demonstrate that CP EDMR inherits one of the most important features of the CP method: the gate control of the energy window of the detectable interface defects for spectroscopy.